Analisis Penerapan PPh 21 Dalam Sistem Penggajian Karyawan Di Era Digital: Studi Kasus Kesalahan Rekonsiliasi Pajak Tahunan Pada Penerapan Tarif Efektif Rata-Rata (TER) - Nadira Aulia Zahra; Oktavia Ramadhani; Rolan Rizki Rinaldi Daulay; Dini Vientiany (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Income tax article 21 (PPh 21) is a tax on income received by employees and is directly deducted by the employer through the payroll system. However, along with advancing technology, the payroll system has shifted from manual to digital, namely the payroll system, as well as the application of the Average Effective Rate that has been used since 2024, to facilitate the calculation of monthly taxes. Nevertheless, in the practice of implementing this TER system, there are still several errors that often occur, particularly regarding the failure to perform annual tax reconciliation, which can result in discrepancies between the amount of tax withheld and the actual obligation. Therefore, this research is conducted to observe and examine how PPh 21 is implemented in the modern payroll system and what errors frequently occur since the implementation of the TER. The method used is a literature study with a qualitative descriptive approach.